1988
DOI: 10.1161/01.atv.8.4.368
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Apo B-100 segments mediating the interaction of low density lipoproteins with arterial proteoglycans.

Abstract: The Interactions of low density llpoproteln (LDL) and apollpoproteln (apo) B-100 segments with chondroltin-6-S0 4 rich aortic proteoglycans aggregate (CSPG) were studied by using quantitative frontal elutlon affinity chromatography. The affinity of the agarose-CSPG was higher for LDL than for very low density llpoproteln, and high density llpoproteln was not bound. LDL from different Individuals had dissociation coefficients (Kd) from 28 to 179 nM. Experiments with tryptlc hydrolysates of apo B suggested that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
93
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(99 citation statements)
references
References 15 publications
4
93
0
1
Order By: Relevance
“…Other evidence in support of this conclusion has been reported. 34 The assay we employed for measuring LDL-proteoglycan binding can be used for examining the inhibitory effects of different proteoglycans or GAGs, as well as lipoproteins, on the interaction. At present, it is not clear, and there are conflicting results concerning the features of proteoglycans that are necessary for LDL binding.…”
Section: Resultsmentioning
confidence: 99%
“…Other evidence in support of this conclusion has been reported. 34 The assay we employed for measuring LDL-proteoglycan binding can be used for examining the inhibitory effects of different proteoglycans or GAGs, as well as lipoproteins, on the interaction. At present, it is not clear, and there are conflicting results concerning the features of proteoglycans that are necessary for LDL binding.…”
Section: Resultsmentioning
confidence: 99%
“…Distinct apo B sequences that bind heparin 39 -40 and CSPG 41 have been identified. Similar heparin-binding sites were reported on apo E. 40 - 42 In the current studies, we have found that a decrease in the apo E to apo B molar ratio of the d=1.015-1.025 g/ml subtraction of LDL from animals fed the fish oil versus lard diet was related to decreased binding of these subfractions to CSPG.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, LDL binds with high affinity to many proteoglycans found in the artery wall. The interaction between LDL and proteoglycans involves basic amino acids in apolipoprotein (apo) B100, the protein moiety of LDL, that interact with the negatively charged glycosaminoglycans [3][4][5] or bridging molecules such as apoE or lipoprotein lipase. 1 Isolation of large fragments of apoB100 from different regions characterized by concentrations of positive clusters indicated that up to 8 specific regions in delipidated apoB100 bind proteoglycans.…”
mentioning
confidence: 99%